Distribution of Skin Prick Test Results in Rhinitis Allergic Patients at Dr. Hasan Sadikin General Hospital Bandung - Antares, Gama; Dermawan, Arif; Permata, Yenti (Althea Medical Journal, 2017)
Background: Allergic Rhinitis (AR) is an inflammation condition in nasal mucous because of type 1 hypersensitivity. Skin prick test is one of the diagnostic tests to diagnose AR. Purpose of this study was to know the distribution of skin prick test in AR patients.Methods: This study used retrospective descriptive method as cross sectional design. This study was performed from 1 August to 31 October 2014. This study used medical record as secondary data at Department of OtorhinolaryngologyâHead and Neck Surgery of Dr. Hasan Sadikin General Hospital. There were 175 cases which fulfilled the inclusion criteria of the study. The data were then analyzed using computer program.Results: Forty seven cases were positive for house dust (26.8%), 127 cases were positive for dust mite (72.5%), 85 cases were positive for rice pollen (48.5%), 62 cases were positive for maize pollen (35.5%), 56 cases were positive for mixed fungi (32%), 100 cases were positive for cockroach (57.1%), 63 cases were positive for horse dander (36%), 50 cases were positive for cat dander (28.5%), 93 cases were positive for dog dander (53.1%), and 38 cases were positive for chicken feather (21.9%).Conclusions: The most aeroallergen making positive result in skin prick test is dust mite. [AMJ.2017;4(1):129â32]Â DOI:Â 10.15850/amj.v4n1.1033